Experience in Using Assessment Tools and e-Learning Quality Management Practices (Case Study of Tomsk State University) - E. S. Goryunova; A. S. Ivanova; A. A. Stepanenko; A. V. Feshchenko (Открытое образование (Москва))
The aim of the study was to analyze the use of assessment tools and the experience of managing the quality of education in the electronic information and educational environment of the university on the example of Tomsk State University in the context of the changes that occurred during the pandemic COVID-19. The relevance of the study is due to the fact that the system of higher education in Russia is developing in the context of a permanent change in the requirements for it, internal and external challenges, which determines the need for a consistent response while maintaining the fundamental foundations of this social institution.Materials and methods. The authors relied on a systematic approach to create a holistic review of the available tools for assessing and managing the quality of e-learning at Tomsk State University, an activity approach to identify the transformation of the range of tools used, depending on the increase in the subjectivity of participants in the educational process. The following methods were used in the work: analysis of pedagogical, scientific, technical and methodological literature on the research problem, systematization, generalization, analysis, observation, statistical methods for processing results.Results. The study summarizes and describes the experience of Tomsk State University in using assessment tools and quality management practices of e-learning at the university before the pandemic COVID-19, which made it possible to effectively switch to a forced remote format of student learning. These are the analysis of educational data obtained based on the learning management system MOODLE, the assessment of the quality of e-learning using feedback, and the expertise of e-learning courses. Also study systematized and described new tools for analyzing, evaluating, monitoring, improving and predicting the quality of e-learning, introduced at the university in the context of the pandemic COVID-19, which together made it possible to lay the foundation for the transition of the university to a blended learning model in the post-pandemic period. These were activity monitoring of the subjects of the educational process with the ranking of the measured index, changes in personnel policy, digital diploma supplement etc. The developed tools make it possible to manage the quality of e-learning based on data, and reach the management of the quality of education as a whole through the “balancing” of the structure and content of all components of the educational program.Conclusion. The system for the implementation of e-learning of Tomsk State University ensured the harmonious integration of educational activities using distance learning technologies into the experience of educational interaction between professors and students. It remains possible to maintain the stability and quality of lectures and practical classes, and often enrich them through the capabilities of digital tools. Further expansion of the set of applied tools for assessing and ensuring the quality of e-learning in the university made it possible to organize a transition to a distance learning format, and created the basis for meaningful consolidation of a mixed learning model at the university in the post-pandemic period.